Fat oxidation rates in professional soccer players - Randell, R. K.; Carter, J. M.; Jeukendrup, A. E.; Lizarraga, M. A.; Yanguas, J. I.; Rollo, I. (Medicine & Science in Sports & Exercise, 2019)
Purpose Large interindividual variation exists in maximal fat oxidation (MFO) rates and the exercise intensity at which it occurs (FATMAX). However, there are no data describing the shape of the fat oxidation curve or if individual differences exist when tested on separate occasions. Furthermore, there are limited data on fat metabolism in professional team sport athletes. Therefore, the aim of this study was to test-retest the concavity (shape) and intercept (height) of fat oxidation curves within a group of professional soccer players.